Comparing the intubation effectiveness of two different laryngoscopes in patients with cerebral palsy - Aysun Çağlar Torun; Mustafa Erhan Sarı; Ersin Köksal; Sevgin İbiş (Cumhuriyet Dental Journal, 2018)
Objective: In patients with expected airway difficulties, specific preparatory and auxiliary equipment is required before general anesthesia. The aim of this study was to compare the intubation efficacy of Macintosh laryngoscope with that of the McGrath MAC video laryngoscope in patients with cerebral palsy.